2010
DOI: 10.1186/1471-230x-10-138
|View full text |Cite
|
Sign up to set email alerts
|

The gene-reduction effect of chromosomal losses detected in gastric cancers

Abstract: BackgroundThe level of loss of heterozygosity (LOH) that reduces a gene dose and exerts a cell-adverse effect is known to be a parameter for the genetic staging of gastric cancers. This study investigated if the cell-adverse effect induced with the gene reduction was a rate-limiting factor for the LOH events in two distinct histologic types of gastric cancers, the diffuse- and intestinal-types.MethodsThe pathologic specimens obtained from 145 gastric cancer patients were examined for the level of LOH using 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Several LOH studies demonstrated that the extent of chromosomal loss appeared to be of prognostic significance (French et al, 2004;Gazvoda et al, 2007;Koo et al, 2004). It was established that there was a trend of two distinct subtypes, high-level LOH (named LOH-H) and low-level LOH (named LOH-L), being correlated with intestinal or mixed and diffuse growth patterns, respectively (Hong et al, 2010). In our study we also found out that LOH-H was associated with intestinal type of gastric cancer .…”
Section: Lohsupporting
confidence: 65%
“…Several LOH studies demonstrated that the extent of chromosomal loss appeared to be of prognostic significance (French et al, 2004;Gazvoda et al, 2007;Koo et al, 2004). It was established that there was a trend of two distinct subtypes, high-level LOH (named LOH-H) and low-level LOH (named LOH-L), being correlated with intestinal or mixed and diffuse growth patterns, respectively (Hong et al, 2010). In our study we also found out that LOH-H was associated with intestinal type of gastric cancer .…”
Section: Lohsupporting
confidence: 65%
“…For example, ROBO1 and ROBO2 at 3p12.3 are regulators of axon guidance, and the expression levels of these genes are frequently suppressed by methylation and/or LOH in many cancer types 38 . CADM2 39 and VGLL3 40 at 3p12.1 also have tumor suppressive functions. Collectively, these results imply that the tumor-suppressor genes at 3p12-pcen are impaired by copy-neutral LOH in DGC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fixation process used for the FFPE tissues could cause DNA fragmentation, damage or fusion, thus leading to a false-negative result. Additionally, considering that loss of chromosome frequently occurred in many cancers can result in genomic chromosomal instability [ 14 16 ], it implies that the loss of the reference gene loci in the tumor may cause a false-positive elevated ratio of MET : AP3B1 in ddPCR, rather than high MET copy number.…”
Section: Discussionmentioning
confidence: 99%